EVALUATION OF UTERINE-PLACENTAL-FETAL CIRCULATION IN PREGNANT WOMEN WITH VARICOSE VEINS OF THE LOWER EXTREMITIES - Paraschuk, Yu.S.; Daoud, Nader Kh. N. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The condition of uterine-placental and fetal circulation was investigated in pregnant with varicose veins of the lower extremities. It was established that the parameters of uterine-placental and fetus circulation are reduced in this pathology. Complex Dollper study of uterine-placental and fetus circulation can be used in early diagnosis of pregnancy complications in women with varicose veins of the lower extremities.